Attention Span in the Digital Generation: Educational Technology Challenges in Maintaining Learning Focus - Nur Wahyuni (PT. Anagata Sembagi Education, 2026)
The digital revolution has profoundly altered the cognitive profiles of contemporary learners, particularly Generation Z and Generation Alpha, leading to measurable declines in sustained attention capacity. This systematic literature review synthesizes evidence from 20 peer-reviewed studies (2021–2024) to examine the challenges that shortened attention spans pose for educational technology (EdTech) and to evaluate strategies that effectively maintain learner focus in digitally saturated environments. Grounded in Cognitive Load Theory, Self-Determination Theory, and attention restoration frameworks, the review identifies digital distraction, driven by social media algorithms, constant device connectivity, and hyper-stimulating content, as the primary mechanism eroding sustained focus. Evidence from neurocognitive studies using EEG and eye-tracking confirms that online learners exhibit significant attentional fatigue within 10–15 minutes of undifferentiated exposure. Effective EdTech interventions identified include microlearning (short-form video ≤5 min), gamification, AI-adaptive learning systems, augmented and virtual reality environments, and AI-powered chatbot tutoring. These strategies collectively improve engagement by 20–35% and knowledge retention by 15–28% compared to traditional instructional formats. The study proposes a four-component framework, Detect, Design, Deliver, and Develop, for sustaining learner attention in digital educational contexts. Findings provide actionable guidance for instructional designers, educators, and EdTech developers navigating the attentional realities of digital-native learners